Summary of CPWF Research in the Limpopo River Basin - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2014)
In 2009, the CGIAR Challenge Program on Water and Food (CPWF) set out to “improve governance and management of rainwater and small water infrastructure in the Limpopo basin to raise productivity, reduce poverty, and improve livelihoods resilience.” Over the following four years, CPWF, led by the Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) and partners, coordinated five inter-connected research- for-development projects in the basin. The program was embedded within partnerships and networks that possessed regional legitimacy and could leverage change in this rapidly developing region. The Limpopo Watercourse Commission (LIMCOM) and the Southern African Development Community (SADC) strongly supported CPWF’s approach in the Limpopo River basin, and both institutions are planning to incorporate CPWF findings into ongoing work.